Adults with autism overestimate the volatility of the sensory environment - Lawson, Rebecca P; Mathys, Christoph; Rees, Geraint (Nature neuroscience, 2017)
The authors address why the use of prior expectations might be compromised in autism, by using computational models and pupillometric markers of the neuromodulator noradrenaline. They show that by estimating the world to be more changeable than it really is, adults with autism have difficulty in learning what to expect. Insistence on sameness and intolerance of change are among the diagnostic criteria for autism spectrum disorder (ASD), but little research has addressed how people with ASD represent and respond to environmental change. Here, behavioral and pupillometric measurements indicated that adults with ASD are less surprised than neurotypical adults when their expectations are violated, and decreased surprise is predictive of greater symptom severity. A hierarchical Bayesian model of learning suggested that in ASD, a tendency to overlearn about volatility in the face of environmental change drives a corresponding reduction in learning about probabilistically aberrant events, thus putatively rendering these events less surprising. Participant-specific modeled estimates of surprise about environmental conditions were linked to pupil size in the ASD group, thus suggesting heightened noradrenergic responsivity in line with compromised neural gain. This study offers insights into the behavioral, algorithmic and physiological mechanisms underlying responses to environmental volatility in ASD.